2017
DOI: 10.1017/s1355617717000157
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Head-to-Head Study of Three Computerized Neurocognitive Assessment Tools Part 2: Utility for Assessment of Mild Traumatic Brain Injury in Emergency Department Patients

Abstract: The CNTs evaluated, developed and widely used to assess sport-related concussion, did not yield significant differences between patients with mTBI versus other injuries. Symptom scores better differentiated groups than CNTs, with effect sizes weaker than those reported in sport-related concussion studies. Nonspecific injury factors, and other characteristics common in ED settings, likely affect CNT performance across trauma patients as a whole and thereby diminish the validity of CNTs for assessing mTBI in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…This study calculated and evaluated seven candidate composite scores for the neuropsychological battery used in the CENTER-TBI. The MTBI sample, on average, performed in the broadly normal range on all of the individual cognitive test scores at 2 weeks post injury ( Table 2 ), which is generally consistent with studies examining neuropsychological outcome at 2 weeks after injury ( 13 16 ) and reflects the favorable cognitive outcome experienced by this sample. Further, there were no statistically significant differences in any of the composite scores, or in the individual tests, when comparing the MTBI, trauma control, and community control groups ( Tables 2 , 7 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study calculated and evaluated seven candidate composite scores for the neuropsychological battery used in the CENTER-TBI. The MTBI sample, on average, performed in the broadly normal range on all of the individual cognitive test scores at 2 weeks post injury ( Table 2 ), which is generally consistent with studies examining neuropsychological outcome at 2 weeks after injury ( 13 16 ) and reflects the favorable cognitive outcome experienced by this sample. Further, there were no statistically significant differences in any of the composite scores, or in the individual tests, when comparing the MTBI, trauma control, and community control groups ( Tables 2 , 7 ).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, as well as in the CENTER-TBI study, patients with mild traumatic brain injury (MTBI) were assessed 2 weeks after the injury. The extent of cognitive deficits 2 weeks after MTBI is uncertain, and empirical studies report effect sizes ranging from very small to medium (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies of cognition at 2 weeks after MTBI, and those identified have produced similar results. [22][23][24][25] Despite the general view that cognitive deficits in patients with MTBI tend to resolve rapidly after injury, subgroups of patients with MTBI may suffer from trauma-related cognitive impairments that might not be revealed by meta-analyses. 20,53 The current study evaluated three subgroups based on indices of injury severity: LOC, PTA, and positive neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] The nature and extent of cognitive deficits during the subacute period, from 2 to 3 weeks following injury, are not well understood because the majority of studies examine other timepoints, such as during the first week or at 1, 3, 6, or 12 months following injury. Meta-analyses report small to medium effect sizes in the period 7 to 30 days post-injury, 10,21 and findings from individual empirical studies on cognitive functioning in patients 2 to 3 weeks post-MTBI commonly report very small to medium effect sizes that often do not reach statistical significance, [22][23][24][25] possibly due to insufficient statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…Future work carried out in the ED can therefore utilise age‐scaled normative data collected for the CANTAB iPad application. A head‐to‐head study comparing performances of three different CNTs including ImPACT (Immediate Post‐Concussion and Cognitive Testing), ANAM and DANA (Automated Neuropsychological Assessment Metrics and Defence Automated Neurobehavioral Assessment) found that all three were unable to distinguish between mTBI and trauma patients within 72 h of injury recruited from a level 1 trauma centre . This supports the use of CANTAB neurocognitive battery and its early implementation within the ED given it could distinguish between the groups.…”
Section: Discussionmentioning
confidence: 77%